Study guides

☆☆

Q: What is 2x plus 1x plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

First add coefficients: * 1x + 1x = 2x Second add the other values: * 4 + 5 = 9 Put it all together!: * 1x + 1x + 4 + 5 = 2x +9 * 2x + 9

2x + 1 = 1x + 11Subtract 1x from each side:1x + 1 = 11Subtract 1 from each side:1x = 10

Simplifying x2 + -2x + -63 Reorder the terms: -63 + -2x + x2 Factor a trinomial. (-7 + -1x)(9 + -1x) Final result: (-7 + -1x)(9 + -1x)

There is always a 1 in front of the x but the 1 is invisible so it same as 1x + 1x = 2x x + x = 2x

6x + 9 + 2x = 8x + 9

Related questions

x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3

First add coefficients: * 1x + 1x = 2x Second add the other values: * 4 + 5 = 9 Put it all together!: * 1x + 1x + 4 + 5 = 2x +9 * 2x + 9

2x + 1 = 1x + 11Subtract 1x from each side:1x + 1 = 11Subtract 1 from each side:1x = 10

x + 6 = 2x - 9 Add 9 to both sides: x + 15 = 2x Subtract 1x from both sides: 15 = 1x or 15 = x

If: x+1+2x = 1x+5 Then: x = 2

Simplifying x2 + -2x + -63 Reorder the terms: -63 + -2x + x2 Factor a trinomial. (-7 + -1x)(9 + -1x) Final result: (-7 + -1x)(9 + -1x)

2x+2=x+6 first subtract 2x. -2x -2x2=-1x+6 then subtract 6-6 -6-4=-1x finally divide by -1x=4 X equals four.

1x + 5

3x

Since x by itself is the same as 1x, the expression can be re-written as 1x+2x Then, ignore the x's and simply add the numbers to obtain 1x+2x=3x 3x is your answer.

3x+9=2x+10 3x+9-2x=10 9+x=10 x=1

There is always a 1 in front of the x but the 1 is invisible so it same as 1x + 1x = 2x x + x = 2x

People also asked